Case Report: Severe thrombocytopenia in the context of concomitant tirofiban and ibuprofen use: does ibuprofen matter? - Zhu, Juxun; Chen, Chao; Zhu, Chenlu; Sun, Lili (Frontiers in Cardiovascular Medicine, 2025)
Tirofiban is a glycoprotein (GP) IIb/IIIa receptor antagonist that inhibits platelet-to-platelet interactions and thrombosis by preventing fibrinogen from binding to platelets. While it has the potential to cause thrombocytopenia and bleeding, instances of severe thrombocytopenia are rare. The question arises whether the concurrent use of tirofiban with other drugs that pose risks to platelets might increase the likelihood of severe platelet depletion. Herein, we present two cases of profound and sudden thrombocytopenia associated with tirofiban use in the treatment of acute progressive stroke. Both patients received ibuprofen for pain relief concomitantly. Drug-induced thrombocytopenia (DITP), a rare but potentially life-threatening adverse effect, occurred. Ibuprofen is a nonsteroidal anti-inflammatory drugs (NSAIDs) with both aspects regarding platelets: function inhibition, responsible for drug-induced thrombocytopenia. We recommend avoiding concomitant use of ibuprofen in patients receiving tirofiban infusion. Alternative analgesics (e.g., acetaminophen/paracetamol) may be considered when pain management is required. If concurrent administration is unavoidable, intensive platelet count monitoring (e.g., every 6–12 h) is imperative during the first 24 h of therapy.